Practice of Chemistry of Chinese Materia Medica Teaching Based on Competency by AI Technology - Li, Na; Sun, Jianbo; Ding, Yiming; Chen, Li (Journal of Educational Research and Policies, 2026)
This study introduces the practice of Chemistry of Chinese Materia Medica teaching, aiming to both strengthen the integration of theory and practice and enhance students’ professional competencies through the application of AI technology. Guided by the core competency requirements for relevant professions, we have restructured the content of the course, introduced innovative teaching models, and optimized the evaluation methods. These reforms specifically include virtual simulation, knowledge graphs, and intelligent evaluation. The implementation of these practices will enhance core competencies of undergraduates in traditional Chinese medicine component analysis, quality control, and research, aligning university education with industry demands and providing a reference for the cultivation of traditional Chinese medicine professionals.